Problem bezdomności w Rzeszowie - Szluz, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Homelessness is a social problem occurring in individual countries, that is becoming more and more recognized, however complex and therefore difficult in the context of conducting scientific research, as well as undertaking initiatives in practice. Scientific publications on this topic had already appeared in Poland during the interwar period. In the Polish People’s Republic it was stressed that the problem was apparently solved by the caring role of the state. The effect of such a declaration was a blurred phenomenon in both popular as well as scientific consciousness. After 1989, homelessness revealed itself anew, resulting in a renewed interest for researchers, as well as creating solutions for practitioners in their efforts in the field of social assistance. Assistance activities are undertaken in Poland by many entities that can be grouped within the public, non-governmental and private sectors. The article presents conclusions from the studies on the phenomenon and scale of homelessness in the city of Rzeszow.
Keywords: homelessness; homeless people; social problems